Large Investors, Price Manipulation, and Limits to Arbitrage: An Anatomy of Market Corners - Allen, Franklin; Litov, Lubomir; Mei, Jianping (Review of Finance, 2006)
Abstract Corners were prevalent in the nineteenth and early twentieth century. We first develop a rational expectations model of corners and show that they can arise as the result of rational behavior. Then, using a novel hand-collected data set, we investigate price and trading behavior around several well-known stock market and commodity corners which occurred between 1863 and 1980. We find strong evidence that large investors and corporate insiders possess market power that allows them to manipulate prices. Manipulation leading to a market corner tends to increase market volatility and has an adverse price impact on other assets. We also find that the presence of large investors makes it risky for would-be short sellers to trade against the mispricing. Therefore, regulators and exchanges need to be concerned about ensuring that corners do not take place since they are accompanied by severe price distortions.